School days : a can-you-find-it book - Schuette, Sarah L., 1976- (Pebble, a Capstone imprint, 2020)
"Treat kids to a seek-and-find celebration! Full-color photo puzzles focused on birthdays, the 100th Day of School, fiestas, and other days people celebrate make finding the hidden objects within them a delightful challenge. Pictographs and word labels are included in each to-find list"--
Ages 4-8
Keywords: Schools -- Juvenile literature; Special days -- Juvenile literature; Picture puzzles -- Juvenile literature